2021
DOI: 10.1002/adom.202100776
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photochemical Switching via Plasmonically Enhanced Upconversion Photoluminescence

Abstract: Photochromic molecule‐incorporated optical devices offer desirable properties for photocontrollable optical systems, including advanced optical data storage and super‐resolution imaging. However, these molecules require multiple illumination sources, such as UV and visible light, for reversible photochemical reactions, which restricts their potential for advanced application. This study reports an effective strategy for modulating photoisomerization via a single near‐infrared light source assisted by plasmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…We note that such a high multicolor switching ratio has been rarely achieved in the reported multi-color uorescence photoswitchable nanoprobes. 36,[53][54][55][56] Previous studies found that uorescent switches fabricated by noncovalently conjugating the uorescence donor with the photochromic acceptor are more favorable for achieving a high switching ratio than that constructed by covalent binding. [57][58][59][60] Thus, instead of covalent conjugation, we adopted a rather mild strategy by physically encapsulating both AuNCs and spiropyran inside lipid NPs.…”
Section: Resultsmentioning
confidence: 99%
“…We note that such a high multicolor switching ratio has been rarely achieved in the reported multi-color uorescence photoswitchable nanoprobes. 36,[53][54][55][56] Previous studies found that uorescent switches fabricated by noncovalently conjugating the uorescence donor with the photochromic acceptor are more favorable for achieving a high switching ratio than that constructed by covalent binding. [57][58][59][60] Thus, instead of covalent conjugation, we adopted a rather mild strategy by physically encapsulating both AuNCs and spiropyran inside lipid NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Single-molecule super-resolution microscopy has become a standard imaging tool for in situ visualization of nanostructures in life sciences [ 120 ], but the application of this technique to polymers has been less explored [ 121 ]. A key bottleneck is the lack of fluorophores and covalent attachment to polymer chains [ 122 ].…”
Section: Diarylethenementioning
confidence: 99%
“…[20][21][22][23][24][25] Intriguingly, the significant development of coreshell structural design over the past few years provides an effective platform for color modulation in a single upconversion nanoparticle by tailoring the emission profiles of different lanthanide centers. [26][27][28][29][30][31][32][33] Despite the enticing prospect, the current development of full-color upconversion nanoparticles is hindered by the harsh need of excitation setup, such as complex three-channel photo upconversion and complicated pulse width modulation. [34][35][36][37] Here, we demonstrate a dual-channel orthogonal upconversion system pumping at 808 nm and 980 nm, in which the specific emissions of different lanthanide dopants can be selectively and exquisitely produced on a single upconversion nanoparticle.…”
Section: Introductionmentioning
confidence: 99%